WAYANG ORANG KALANGAN ELITE KUNTI NALIBROTO - Dhita Anindya Widyarani (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2013)
The existence of Wayang Orang (a form of traditional Javanese stage show) in Jakarta is characterized by the involvementof the elite community who, as both performers and funders, make it possible for the art of Wayang Orang to continue to existand develop. The Kunti Nalibroto troupe, one of the elite Wayang Orang groups in Jakarta, was chosen as the object of thestudy, with the aim of discovering various facts related to the existence of Wayang Orang groups among the elite communityin Jakarta. The formulation of the problems addressed in this research is as follows: (1) Why do the elite choose the art ofWayang Orang as a way of self expression? (2) What is the concept of Wayang Orang among the elite community of KuntiNalibroto? (3) What is the potential of the elite Kunti Nalibroto Wayang Orang group? Within the conceptual framework,the concepts used are concepts of ‘role’, ‘status’, and ‘elite community’. The research uses an analytical descriptive methodwith a qualitative and phenomenological approach to outline the characteristics and facts about the Wayang Orang groupsamong elite community in Jakarta. The techniques used for collecting data included a bibliographical study, observation, andinterviews. From the results of the study, it can be concluded that: (1) The elite choose Wayang Orang as a means of selfexpression because they need an activity for relaxation in order to maintain a balanced life, and by practicing Wayang Orangthey are able to return to their traditional cultural roots and cultivate their spiritual, sensory, and physical needs; (2) TheKunti Nalibroto Wayang Orang group is a non-profit organization whose members all belong to the elite female community(socialites) and who aim to support the development of the traditional arts by holding regular Wayang Orang performances;(3) All the potential of this group is displayed to a maximum in Kunti Nalibroto’s performances, and in the future this grouphas the potential to continue to exist in the world of Wayang Orang and to make a contribution to the preservation anddevelopment of the art of Wayang Orang in Indonesia.Keywords: Wayang Orang, elite, Kunti Nalibroto.